Practices in the pig value chain in Uganda; implications to African swine fever transmission - Muhangi, D.; Masembe, C.; Berg, M.; Ståhl, K.; Ocaido, M. (Livestock research for rural development, 2014)
Uganda has the largest pig industry in eastern Africa, with majority of farmers still smallholders. African swine fever (ASF) is arguably one of the major constraints in the region, where it is considered endemic. Although the sylvatic cycle exists here, the pig-pig cycle of transmission is more important. The pig value chain is one critical area where there is need for study of the role it plays in the spread of ASF. In this study, different practices and their association with the transmission of ASF within and between farms were investigated on 101 pig farms in Uganda. Practices by 30 traders in pigs and pig products (slaughter slab, pork butchery and roasted pork restaurant operators) were investigated in the districts of Kabarole, Mityana, Moyo, Mukono, Soroti, and Tororo. Key informant interviews with the District Veterinary Officers (DVOs) about pig trade, pig slaughter infrastructure, ASF status and its Management in the districts were conducted as well between May-November 2011. Questionnaires were administered to both pig farmers and the traders.Twenty six percent of the farmers reported having had the disease on the farm in the last one year.Although none of the risk factors was statistically significant for ASF outbreaks, results demonstrated presence of potential risk factors for ASF on the farms and the rest of the pig value chain.
Keywords: ASF, pig farms, pigs, risk factors, traders